NAFLD and Diabetes: Two Sides of the Same Coin? Rationale for Gene-Based Personalized NAFLD Treatment - Xia, Ming-Feng; Bian, Hua; Gao, Xin (Frontiers in Pharmacology, 2019)
The prevalence of non-alcoholic fatty liver disease (NAFLD) has been increasing rapidly and at the forefront of worldwide concern. Characterized by excessive fat accumulation in the liver, NAFLD regularly coexists with metabolic disorders, including type 2 diabetes, obesity, and cardiovascular disease. It has been well established that the presence of NAFLD increases the incidence of type 2 diabetes, while diabetes aggravates NAFLD to more severe forms of steatohepatitis, cirrhosis, and hepatocellular carcinoma. However, recent progress on the genotype/phenotype relationships in NAFLD patients indicates the development of NAFLD with a relative conservation of glucose metabolism in individuals with specific gene variants, such as the patatin-like phospholipase domain-containing 3 (PNPLA3) and transmembrane 6 superfamily member 2 protein (TM6SF2) variants. This review will focus on the clinical and pathophysiological connections between NAFLD and type 2 diabetes and will also discuss a disproportionate progression of NAFLD and diabetes, and the different responses to lifestyle and drug intervention in NAFLD patients with specific gene variants that may give insight into personalized treatment for NAFLD.